Social security as a monopoly - André Drost; Bernhard Felderer (Institute for Advanced Studies (IHS), 2001)
The typical social security program is designed as follows: (1) It is organized as a pay-asyou-go system. (2) It is financed with a payroll tax. (3) Employers and employees share the tax. (4) Benefits are largely independent of asset income. (5) Benefits are increasing with the taxes paid. (6) Benefits induce retirement. We present a model that can explain these stylized facts. Our model refers to an economy where workers want to monopolize the labor market. For this purpose, they bring about a social security act, which requires old workers to retire and young workers to pay transfers to retirees. The first prescription serves to reduce labor supply in order to realize a monopoly gain. The second prescription serves to give old workers share to the gain. As we will show, the social security program emerging in our model is similar to the typical program described above.
Keywords: H55; 330; social security; public pensions; political economy; monopolistic labor market; Nash bargaining solution; Gesetzliche Rentenversicherung; Theorie